Two-fraction stereotactic ablative radiotherapy (SABR) versus two-fraction high dose rate (HDR) brachytherapy for localized prostate cancer: Does dose heterogeneity matter?. (April 2022) - Correa, Rohann J.M.; Morton, Gerard; Chung, Hans T.; Tseng, Chia-Lin; Cheung, Patrick; Chu, William; Liu, Stanley K; McGuffin, Merrylee; Shahid, Anam; Davidson, Melanie; Ravi, Ananth; Helou, Joelle; et al.
Highlights: PSA kinetics and biochemical failure were similar with two-fractions of SABR or HDR. Quality of life, acute and late toxicities were no different in the two cohorts. These data support the design of RCTs comparing these treatment approaches. Abstract: Background and purpose: Contemporary radiotherapy for localized prostate cancer (PCa) is deliverable via stereotactic ablative radiotherapy (SABR) and high dose rate (HDR) brachytherapy. Here we report on a parallel cohort analysis of two prospective, phase II clinical trials of two-fraction prostate SABR versus two-fraction HDR monotherapy. Materials and methods: Enrolled patients had histologically-confirmed PCa (clinical stage T1c-T2b; grade group 1, 2, or 3; and PSA < 20 ng/mL). SABR and HDR doses were 26 Gy and 27 Gy in 2 weekly fractions, respectively. Patient-level data from each cohort was analysed to assess prostate specific antigen (PSA) response kinetics, biochemical failure, toxicity, and quality of life (QOL). Results: Thirty patients receiving SABR and 83 receiving HDR were included. Fifty percent and 30% of patients had unfavourable-intermediate risk disease, respectively. SABR patients had higher mean baseline PSA (8.7 versus 6.8 ng/mL, p = 0.016). Median follow-up was 72.7 and 65.3 months, respectively. Mean dose delivered ( D mean ) was 26.6–26.8 Gy for SABR versus 35.5–45.5 Gy for HDR. Both cohorts achieved a median nadir PSA of 0.16 ng/mL at a median of 57 months post-treatment. Cumulative biochemical failure probability (±SE) at 72 months was 3.5% (±3.5%) for SABR versus 12.8% (±4.8%) for HDR ( p = 0.19). Low rates of CTCAE grade ≥2 toxicity were observed in both cohorts. No differences in EPIC scores over time were observed between cohorts. Conclusions: Two-fraction SABR yields similar rates of biochemical failure, acute and late toxicities, and QOL as two-faction HDR brachytherapy. These data support the design of a randomized controlled trial comparing these treatments.